Meta-Analysis of Challenges and Solutions in Early Childhood Education in Indonesia - Faiza A. Dali,; Anton Kaharu,; Rusmin Husain, (International Journal of Scientific Research in Science and Technology, 2025)
Early childhood education faces many complex challenges in this digital era. This study conducted a meta-analysis of 20 SINTA-indexed journals to identify the main challenges faced by early childhood education teachers and the latest solutions that can be applied. The results of the analysis show that the biggest challenges include innovative curriculum development (52%), collaboration with parents (14%), adapting to technology and the digital era (10%), improving professionalism (10%), conducive learning environment (10%), and managing technology use (5%). Proposed solutions include intensive training for teachers, integration of STEAM-based curriculum, and development of wise technology use policies. This article provides practical guidelines for improving the quality of early childhood education.
Keywords: Early childhood education; teacher challenges; innovative curriculum; educational technology; parent collaboration; teacher professionalism